Bibliometric Mapping of Earnings Management Research - Judijanto, Loso; Ali, Fifitri (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of earnings management research spanning the period from 2000 to 2025. Utilizing data from the Scopus database and analytical tools in VOSviewer, the study explores the thematic structure, intellectual foundations, and collaborative networks within the field. The keyword co-occurrence analysis reveals that core concepts such as discretionary accruals, audit quality, and financial reporting quality continue to dominate the literature, while newer themes like sustainability, corporate social responsibility, and gender diversity are emerging as significant research frontiers. Temporal and density visualizations indicate a shift from traditional earnings manipulation techniques toward broader governance and ethical considerations. The co-authorship and country collaboration networks highlight influential scholars and the dominance of the United States, China, and the United Kingdom, alongside increasing contributions from emerging economies. This bibliometric mapping not only consolidates existing knowledge but also provides a strategic overview of future research directions in the evolving landscape of earnings management.